Suppression of Mutual Coupling Between Two Microstrip Patch Antennas using a Sophisticated Non-Linear DGS Structure for High Frequency Wave Applications - Gupta, Lavesh; Dwivedi, Arun Dev Dhar (Law, State and Telecommunications Review, 2018)
Purpose ”“ If the two or more than two antennas are present in the antenna array, the mutual coupling between them becomes a critical issue to deal with. At microwave frequency, microstrip design is often used as a transmission line because of its good performance in transferring the energy and microwave signals. Most commonly used microstrip antenna has similar structure as that of the microstrip line. On one side of dielectric substrate layer, is an extremely thin layer of conductor that forms the radiating elements and on bottom side is the ground plane made up of metallic material. Our main motive is to maintain mutual coupling suppressing structure to its simplest form. Methodology/approach/design ”“ We therefore use a Defected Ground Structure (DGS), which greatly decreases the mutual coupling between the two antennas, thus enhancing the performance of the antenna array. Findings ”“ The introduction of the DGS does not affect the characteristics of antenna array system. The Simulation is done using CST (Computer Simulation Technology) software and the results are tested using Vector Network Analyzer. Both the simulated and measured results are in good agreement. The coupling has been reduced from -22 to -37 dB. The recent boom in wireless industry has led to the demand for the multiband antennas.